3. Framing Consciousness Studies. - MINISSALE, GREGORY (Consciousness, Literature & the Arts (1573-2193), 2009)
The article looks at various models of consciousness, notions of symmetry and parallel processes, structure of higher-order thoughts, stream, and self-consciousness that use the underlying logic of framing and the frame-in-the-frame. It cites the most commonly used methods for describing the operation of lower forms of consciousness. The external marks of art reportedly express the cooperation of mental processes which produce vision. The significance of the inductive reasoning about conscious processes to understanding visual art is noted.